Molecular organization of functionalized carbon nanotube at the water-air interface and in solid thin film - de Oliveira, Vinicius Jessé Rodrigues [UNESP]; da Silva, Edilene Assunção [UNESP]; de Almeida Olivati, Clarissa [UNESP] (FapUNIFESP (SciELO), 2021)
Carbon Nanotubes (CNTs) are materials of wide applicability, either due to their physical stability, rigidity of the structure and/or high electrical conductivity. These nanotubes can be manipulated using different techniques, as long as their idiosyncrasy and possible advantages of proper processing are known. One way to organize and manipulate this material is in the form of thin films, which despite the low solubility in organic solvents, when functionalized, the CNTs allow for satisfactory handling. In this work, we aimed to analyze the behavior of CNTs in an aqueous subphase, controlling the quality of the produced films. For that, it was observed the level of aggregation and rigidity of Langmuir films and carried out analyses of the monolayer reorganization and interaction of the mixture between CNTs and Stearic Acid. Quantitative estimations of the aforementioned features were done through an in-situ study that was performed using the Langmuir technique including analysis of isotherms, compressibility module, Gibbs interaction, and Brewster Angle Microscopy. In order to compare the monolayer after its removal from the Langmuir trough, UV-vis spectroscopy was carried out. The results showed that they form non-ideal mixtures, but they favor a better organized and less agglomerated film comparing to the pure CNT.
Keywords: Carbon nanotube; Langmuir; Monolayer; Thin Films